Incorporating vehicle trails in soil moisture downscaling for mobility assessments in coarse grained soils - Proulx, Holly E., author; Niemann, Jeffrey D., advisor; Scalia, Joseph, advisor; Lynn, Stacy, committee member (Colorado State University. Libraries, 2024)
Fine resolution (10-30 m) soil moisture maps are critical for determining vehicle mobility in agricultural, forestry, recreational, and military applications. Microwave satellites provide soil moisture products, but the spatial resolutions of these products are too coarse for such applications. Soil moisture downscaling methods, such as the Equilibrium Moisture from Topography Plus Vegetation and Soil (EMT+VS) model, can downscale soil moisture to fine resolutions. However, the EMT+VS model (like most other downscaling models) does not explicitly consider vehicle trails, which may have different soil moisture than undisturbed landscape locations. The objective of this study is to generalize the EMT+VS model to explicitly estimate the soil moisture of trails. The generalized model incorporates two hypothesized effects of vehicle traffic on trails (reduced vegetation cover and reduced porosity). To evaluate the generalized model, porosity and soil moisture observations were collected across a study region in the foothills of the Colorado Front Range. Data were collected at paired trail and landscape locations as well as unpaired landscape locations on six dates in Summer 2023. On average, the porosity of the trail locations was 86% of the paired landscape locations. Soil moisture on trails was on average 73% to 88% of the moisture of the paired landscape locations. Including the vegetation and porosity adjustments in the EMT+VS model reduced the tendency of the model to overestimate the moisture on trails and improved the root mean squared errors.